Narratives of heritage and legacy: Child and adolescent mental health trainees portrayed - Ayotunde, Ayobello; Siegel, Karen; Feibel, Adelaide; Benoit, Laelia; Martin, Andrés (Frontiers in Child and Adolescent Psychiatry, 2023)
Objectives We sought to embellish a child and adolescent mental health space by creating and displaying a large painting imbued with meaning and symbolism specific to the field. In it, we featured a broad array of trainees in the disciplines of child psychiatry, psychology, and social work. We used the portraiture sessions as opportunities for participants to reflect on their professional trajectories and developmental progression. Methods The lead author painted Heritage and Legacy, a 6 x 4 ft oil painting of 16 trainees (9 women), between February 2020 and December 2022. Each studio sitting lasted approximately four hours and included an in-depth interview that was recorded and transcribed for qualitative analysis. We used narrative inquiry as analytic approach, as it is a method that attends to unique life stories and aims to make meaning out of individual’s experiences. Results We organized our analytic framework chronologically: 1) Heritage (past influences); 2) Becoming (the current process of professionalization); and 3) Legacy (reflections about the future). Through these life stages, we consider findings from three complementary vantage points: 1) the unique methodology of using a collective portrait as the basis for a qualitative study using narrative inquiry; 2) the participants’ individual and collective trajectories of professionalization and professional identity formation; and 3) their transitions and legacy—including through mentorship and generativity, as much as through concrete objects and places, such as the oil painting itself and the space in which it will permanently reside. Conclusions The lengthy process of creating an oil canvas depicting a multidisciplinary group of professionals in training proved a powerful vehicle for self-reflection by those portrayed. It has yielded insights of broader relevance to the training and education of the next generation of their peers.